Effectiveness of Non-Pharmacological Interventions for Irritable Bowel Syndrome: A Systematic Review. (8th November 2021) - Amsallem, Florent; Sanchez, Stéphane; Armoiry, Xavier; Mion, François
Abstract : Introduction . Given the complexity of the therapeutic management of irritable bowel syndrome (IBS), alternative non-pharmacological therapies are frequently offered to patients. The aim of this study was to conduct a systematic review in order to establish the current evidence base for non-pharmacological interventions (body-directed and mind-body therapies) in the management of IBS. Materials and Methods . The literature was searched in several electronic databases (PubMed (including Medline), Web of Science (Clarivate Analytics), Scopus (Elsevier), ScienceDirect (Elsevier), Cochrane Library (Wiley), and Wiley Online Library (Wiley)) for randomized controlled trials (RCTs) published in the English language from 1990 to 2020. Effectiveness outcomes were examined through the change in overall IBS symptoms or abdominal pain up to 12 months after treatment. Results . 11 studies (parallel-group RCTs) were identified that enrolled 1590 participants in total. Body-directed therapies (acupuncture and osteopathic medicine) showed a beneficial effect compared with standard medical treatment for overall IBS symptoms at 6 months follow-up, while no study found any difference between body-directed and sham therapies for abdominal pain or overall IBS symptoms. It was not possible to conclude whether hypnotherapy was superior to standard medical treatment or supportive therapy for overall IBS symptoms or abdominal pain due to discordant results. Conclusions . Although body-directed therapies such as acupuncture and osteopathic medicine may be beneficial for overall IBS symptoms, higher-quality RCTs are needed to establish the clinical benefit of non-pharmacological interventions for IBS. An important challenge will be the definition of the optimal control groups to be used in non-pharmacological trials.